An Optimized PI Controller-Based SEPIC Converter for Microgrid-Interactive Hybrid Renewable Power Sources. (29th June 2022) - Mohanta, Harish Chandra; Geetha, B. T.; Alzaidi, Mohammed S.; Dhanoa, Inderjit Singh; Bhambri, Pankaj; Mamodiya, Udit; Akwafo, Reynah
Abstract : With the use of hybrid renewable sources for example solar and wind turbines, an autonomous electric power generation system based on self-sufficient electric power generation is built in order to promote a smart and ecologically friendly environment. The three-phase inverter that links this scattered generating unit to the grid is in charge of ensuring that it is properly connected to the grid. While the energy produced by the hybrid unit is being utilized, it is also being stored in the batteries so that it may be used to transport power when other sources of power are not available, such as when the grid is down. This stand-alone power conversion and storage system is being built with the aid of power electronic converters and controllers, among other components, in order to ensure balanced power flow operation. To produce PWM pulses for the generator side converter, a PI controller is utilized. On the PV side, an improved PI controller is used to drive the SEPIC converter, which increases the transient responsiveness of the converter while it is being controlled by the controller. In order to communicate with the grid, the generated electricity is routed via a three-phase inverter that is controlled according to the DQ theory. The challenges connected with poor power quality are substantially resolved by the converters that have been presented. For simplicity of use, an automated control function has been introduced; in addition, an interactive MATLAB model of the system is being developed for minor and medium-scale microgrid applications; also, a prototype is being created to verify the simulation results.